Athanasius Raczyński (1788-1874). Aristocrat, Diplomat, and Patron of the Arts - Mencfel, Michał (Brill, 2022)
This book depicts the long rich life and wide ranging work of Count Athanasius Raczyński (1788-1874). By exploring his complex personality, his processes of thought and his accomplishments, it reveals a man at once a wealthy aristocrat, a Pole in the Prussian diplomatic service, an active participant in and perceptive observer and critical commentator on political life, a connoisseur and art collector of European renown, and the author of ground breaking studies on German and Portuguese art - in short a distinguished and fascinating nineteenth century figure.